Mapping Islamic Legal Discourses on Domestic Violence: Media Representation and the Dynamics of Contemporary Muslim Family Law - Sheila Fakhria; Fatimatuz Zahra; Citra Orwela (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Purpose – This study aims to analyze the legal opinions of Instagram users regarding domestic violence (DV) in Muslim families. The study focuses on how elite figures such as religious leaders, politicians, and influencers express their legal opinions on social media, as well as how these opinions are received, responded to, and reconstructed by netizens. Methods – This study uses a qualitative-descriptive approach with Norman Fairclough's critical discourse analysis method. Data was obtained from content on Instagram social media that displayed legal opinions related to domestic violence, including comments from responding netizens. The data was analyzed through three dimensions: text, discourse practice, and sociocultural practice. Findings – The results of the study show that netizens do not necessarily accept legal opinions expressed by elite figures on social media as the sole truth. Instead, netizens actively represent their own understanding, which is often contradictory to the content being presented. The branding of content figures and their ideological backgrounds greatly influence the content and manner of delivery of these legal opinions. Netizens' comments indicate that the digital public sphere plays a significant role in breaking the dominance of patriarchal discourse and creating more emancipatory legal production that focuses on victim protection. Research limitations – The limitation of this study lies in the direct influence of social media content on the public's understanding of the law. Originality/value – This study contributes new insights to the study of Islamic family law and social media by examining the paradigm shift in legal communication in the digital space.